PERAN SINGLE PARENT DALAM PEMENUHAN KEBUTUHAN KELUARGA DI TENGAH PANDEMI COVID-19 (STUDI DI DESA ANDOOLO UTAMA, KECAMATAN BUKE, KABUPATEN KONAWE SELATAN) - Maulana, Ryan Fajar; Tawulo, Megawati Asrul; Jabar, Aryuni Salpiana (Universitas Halu Oleo, 2022)
This study aims to identify and describe the role of single parents in meeting family needs in the midst of the Covid-19 pandemic and explain the efforts made by single parents in meeting their needs. family in the midst of the Covid-19 pandemic in Andoolo Utama Village, Buke District, South Konawe Regency, this study used a descriptive qualitative method on 9 single parents (mother) informants determined by purposive sampling technique, data analysis technique consisted of data collection, reduction data, presentation of data and drawing conclusions / verification, the data obtained were analyzed qualitatively and described in descriptive form. The results showed that the role of single parents from the aspect of traditional roles there were those who had to work alone and those who were assisted by their children and their parents in taking care of housework, from the aspect of transitional roles, in earningliving asingle parents are able to adapt even though it is quite stumbling to carry out their daily professions to earn income without having to worry about the risk of virus transmission, with the help of the social safety net program by providing social assistance it makes a sense of worry and fear to survive in the midst of the Covid-19 pandemic can be helped and reduced a little, from the aspect of the productive role of single parents still doing productive things, not leaving their routine in meeting their family's needs, they are still doing their daily activities as a source of income/livelihood , from the aspect of social roles, in addition to conducting social interactions by greeting neighbors and people in the village, single parents are also active in participating in other social activities in the community, this they do to stay afloat. to stay in touch with the surrounding community, exchange experiences and so that their existence is still recognized and not underestimated. Efforts made by single parents in meeting family needs in the midst of the Covid-19 pandemic are being proactive in seeking information about assistance during the Covid-19 pandemic, saving money, seeking double income by implementing a double income pattern, either as laborers, household assistants, selling/mortgaging. valuables belonging to him, taking credit at financial institutions to be used as business capital and sending their children to school, as well as borrowing from neighbors and taking debt at the nearest shop, conditions are different for single parents who work as civil servants they can work from home relying on a high salary. received every month to meet family needs in the midst of the COVID-19 pandemic.